Peran Perempuan Dalam Melestarikan Nilai-Nilai Moral Tradisional Pada Masyarakat Jepang - Sudarsih, Sri (KIRYOKU, 2021)
The purpose of this study is to explore traditional moral values in Japanese society that are able to survive and be implemented in everyday life in the modern era. In addition, it is able to shape the distinctive character of the Japanese, including the role of women who contribute to maintaining traditional moral values. This research is a qualitative research field of philosophy with the object of formal values and the material object is the development of women's position in Japanese society. The results achieved in the study: Japanese women played an important role in the history of the struggle until Japan achieved prosperity and glory until now. This is based on the reason that Japanese women are able to maintain and preserve traditional moral values that still exist through early education in the family environment. These values can shape the character of children from an early age in the family. A family with character brings logical consequences to the life of a community with character so that it affects the culture as a whole.